The neutrophil-to-lymphocyte ratio as a prognostic biomarker in Guillain-Barre syndrome: a systematic review with meta-analysis - Cabanillas-Lazo, Miguel; Quispe-Vicuña, Carlos; Cruzalegui-Bazán, Claudia; Pascual-Guevara, Milagros; Mori-Quispe, Nicanor; Alva-Diaz, Carlos (Frontiers in Neurology, 2023)
Background and objectives Guillain-Barre syndrome (GBS) is an immune-mediated neuropathy. This has raised the possibility that the neutrophil-lymphocyte ratio (NLR) may be a biomarker of its activity. We conducted a systematic review and meta-analysis to summarize the evidence of NLR as a potential biomarker for GBS. Methods We systematically searched databases (PubMed, Ovid-Medline, Embase, Scopus, Web of Science, SciELO Citation Index, LILACS, and Google Scholar) until October 2021 for studies evaluating pre-treatment NLR values in GBS patients. A meta-analysis using a random-effects model to estimate pooled effects was realized for each outcome and a narrative synthesis when this was not possible. Subgroup and sensitivity analysis were realized. GRADE criteria were used to identify the certainty of evidence for each result. Results Ten studies from 745 originally included were selected. Regarding GBS patients versus healthy controls, a meta-analysis of six studies (968 patients) demonstrated a significant increase in NLR values in GBS patients (MD: 1.76; 95% CI: 1.29, 2.24; I2 = 86%) with moderate certainty due to heterogeneity of GBS diagnosis criteria used. Regarding GBS prognosis, assessed by Hughes Score ≥ 3, NLR had a sensitivity between 67.3 and 81.5 and a specificity between 67.3 and 87.5 with low certainty due to imprecision, and heterogeneity. In relation to respiratory failure, NLR had a sensitivity of 86.5 and specificity of 68.2 with high and moderate certainty, respectively. Discussion With moderate certainty, mean NLR is higher in GBS patients compared to healthy controls. Furthermore, we found that NLR could be a prognostic factor for disability and respiratory failure with low and moderate certainty, respectively. These results may prove useful for NLR in GBS patients; however, further research is needed. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42021285212.